Cultivo da microalga Spirulina platensis em Raceway para a obtenção de matéria-prima para produção do bioetanol - Magro, Francisco Gerhardt (2016)
The search for renewable energy sources was boosted in recent decades, as the sources of non-renewable fuels tend to run out, thus resulting in the search for biofuels made from biomass of microorganisms such as microalgae. Biofuel production this form becomes viable as it can be done on land with low agricultural potential. However, the production on a large scale, necessary for the implementation of the algal biofuel industry, have several limitation. The most widespread technology for the large scale cultivation of microalgae are the raceways, and these photobioreactors, some factors, such as the stirring process, the definition of the cycles of light and fine dark, photoinhibition, the reduction of sedimentation and maximization productivities, need to be studied. The objective was to develop a strategy increase in microalgae production scale Spirulina platensis grown in raceways for the use of biomass and extracellular carbohydrate (soluble) aimed at the production of bioethanol. The completion of the experiment was carried out in mini raceways and pilot plant. The flow was simulated in miniature raceways which were made of acrylic with stirring system in the form of blades. The microalgae Spirulina platensis LEB 52 was used, Zarrouk grown in medium under conditions appropriate for the accumulation of carbohydrates. At the end of the stationary phase and decline in cultivation, the biomass was used for determination of carbohydrates, lipids and proteins. In the resulting liquid centrifuge process it was also determined in exopolysaccharides carbohydrate or soluble in the culture medium. As a result it is possible to report that the stirring speed affect cell concentration, for cultivation at a lower rate (0.10 to 0.15 m.s-1) had a lower concentration, due to the larger volume in the raceway stagnant zones. The stirring rate and the growing phase influence the carbohydrate concentration in the cell, at the speeds of 0.10 and 0.15 m.s-1 the amount of intracellular carbohydrate were lower than those cultured with increasing speeds in both phases of cultivation. Biomass grown until early decline phase showed a higher concentration of carbohydrates due to greater restriction of nutrients, which may have impacted positively on carbohydrate accumulation. Protein concentrations obtained an inverse relationship with the concentration of carbohydrates. The concentration of extracellular carbohydrates was higher in all experiments in the decline phase of cultivation, which sets that were more produced in stationary cultivation phase, or that extracellular carbohydrate is not only from the exopolysaccharides, but cell carbohydrate that has been released. Cultivation was carried out in the raceway with volume of 250 L, reached the concentration of biomass in stationary phase of 1.10±0.004 g.L-1, the performance was lower as compared to mini raceway because the depth of the fluid which limited the incoming light by the cells. The lowest concentration of carbohydrate in the pilot plant compared raceway cultivation performed in mini raceway. The extracellular concentration of carbohydrates resembling the cultivation in the mini raceways where the decline phase yielded the highest concentration